The First Ten K R Narayanan Orations : Essays by Eminent Persons on the Rapidly Transforming Indian Economy - Jha, Raghbendra (Canberra ANU Press, 2006)
Politics and government; Economic conditions; Economic policy; India
English
Keywords: Politics & government; india; politics and government; economic conditions; economic policy; Economic growth; India